Dynamic Simulation and Optimization of Rhombic Drive Stirling Engine Using MSC ADAMS Software. (2016) - Badr, W.S.; Fanni, M.; Abdel-Rahman, Ali K.; Rasoul, S. Abdel
Abstract: In this work, a Beta type Stirling engine with rhombic drive is simulated and optimized using MSC ADAMS software to enhance engine performance. Schmidt model is adopted to determine the instantaneous gas pressure. Hence, the exerted forces on the power piston can be calculated. The model is designed with low to moderate temperature difference in order to facilitate the use of low cost evacuated tubes solar collector. This is in contrast to the use of high cost double axes tracking parabolic dish concentrator that results high temperature difference. All gas forces, friction forces at joints, masses and inertias as well as temperatures of expansion and compression chambers were considered in the model. Simulation at different external loads are carried out and Power-Speed curves for the engine are obtained. The performance optimization based on the dynamic model obtained from the software is formulated. The dimensions of all rhomboid mechanism links, diameters of displacer and piston, and the length of displacer are set as the design variables. The masses and the inertias of the links are set as function of their lengths to account for the variation of the links' dimensions during optimization. The mass of the working gas is kept constant to maintain the input energy at certain value. Results showed that a great increase in the output power could be achieved by optimizing the geometrical parameter of the engine drive.